Typology and universals - Croft, William (Cambridge University Press, 2003)
The second edition of this essential textbook has been thoroughly rewritten and updated to reflect advances in typology and universals over the past decade. It reviews new methodologies such as the semantic map model and questions of syntactic argumentation; discussion of current debates over explanations for specific classes of universals; and comparison of the typological and generative approaches to language.